Mutations in GABRB3: from febrile seizures to epileptic encephalopathies - Møller, Rikke S.; Syrbe, Steffen (Neurology, 2017)
Objective: To examine the role of mutations in GABRB3 encoding the b3 subunit of the GABAA receptor in individual patients with epilepsy with regard to causality, the spectrum of genetic variants, their pathophysiology, and associated phenotypes. Methods: We performed massive parallel sequencing of GABRB3 in 416 patients with a range of epileptic encephalopathies and childhood-onset epilepsies and recruited additional patients with epilepsy with GABRB3 mutations from other research and diagnostic programs. Results: We identified 22 patients with heterozygous mutations in GABRB3, including 3 probands from multiplex families. The phenotypic spectrum of the mutation carriers ranged from simple febrile seizures, genetic epilepsies with febrile seizures plus, and epilepsy with myoclonic-atonic seizures to West syndrome and other types of severe, early-onset epileptic encephalopathies. Electrophysiologic analysis of 7 mutations in Xenopus laevis oocytes, using coexpression of wild-type or mutant b3, together with a5 and g2s subunits and an automated 2-microelectrode voltage-clamp system, revealed reduced GABA-induced current amplitudes or GABA sensitivity for 5 of 7 mutations. Conclusions: Our results indicate that GABRB3 mutations are associated with a broad phenotypic spectrum of epilepsies and that reduced receptor function causing GABAergic disinhibition represents the relevant disease mechanism.